'Going blended': experiences from the implementation of blended learning design and the perspective of a model. (4th December 2009) - Liotsios, K.; Demetriadis, S.
This study discusses the design and implementation of blended learning activities at graduate level, in an effort to explore the potential of this approach to flexibly address student needs. The course was offered twice (in consecutive semesters), implementing varied blending proportions of traditional onsite sessions and web-based asynchronous learning activities. Research results indicate that there are at least three important factors strengthening the efficiency of the blended design, namely: a) introduction of blended activities that engage students in productive learning experiences; b) selection of media that fit to the characteristics of the learning activity; c) accomplishment of a balance between onsite and online activities so that teacher-student dialogue does not result in work overload with detrimental effects for learning. These factors are further determined as the 'cohesiveness', 'media suitability' and 'transactional distance' dimensions of a proposed theoretical construction aiming at modelling the transition process from fully onsite to blended design.